2017
DOI: 10.1051/0004-6361/201629066
|View full text |Cite
|
Sign up to set email alerts
|

HC3N observations of nearby galaxies

Abstract: Aims. We aim to systematically study the properties of the different transitions of the dense molecular gas tracer HC 3 N in galaxies. Methods. We have conducted single-dish observations of HC 3 N emission lines towards a sample of nearby gas-rich galaxies. HC 3 N(J = 2−1) was observed in 20 galaxies with the Effelsberg 100-m telescope. HC 3 N(J = 24−23) was observed in nine galaxies with the 10-m Submillimeter Telescope (SMT). Results. HC 3 N 2−1 is detected in three galaxies: IC 342, M 66, and NGC 660 (>3σ).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…However, this nondetection is expected; the energy of the first excited state is low (0.44 K) with a small Einstein coefficient, so the transition is expected to be significantly weaker than the higher J transitions for the reasonably warm temperatures and high densities in NGC 253. Our nondetections are consistent the weakness of the 2-1 transitions observed in other galaxies (Jiang et al 2017).…”
Section: Unidentified Line In Ngc 253supporting
confidence: 91%
See 1 more Smart Citation
“…However, this nondetection is expected; the energy of the first excited state is low (0.44 K) with a small Einstein coefficient, so the transition is expected to be significantly weaker than the higher J transitions for the reasonably warm temperatures and high densities in NGC 253. Our nondetections are consistent the weakness of the 2-1 transitions observed in other galaxies (Jiang et al 2017).…”
Section: Unidentified Line In Ngc 253supporting
confidence: 91%
“…Meier & Turner 2005) have been studied extensively in extragalactic sources through transitions at higher frequencies, and their transitions at lower frequencies have been detected in Galactic sources. No previous studies of these transitions within our observed bands exist from extragalactic sources, and even the HC 3 N transitions at 18 GHz and 45 GHz has only recently been detected in several nearby galaxies (Meier et al 2011;Jiang et al 2017).…”
Section: Unidentified Line In Ngc 253mentioning
confidence: 64%
“…Various rotational J-transition emission lines of HC 3 N were detected in active galaxies (e.g., Aalto et al 2002;Wang et al 2004;Aalto et al 2007a;Aladro et al 2011;Lindberg et al 2011;Meier et al 2011;Aladro et al 2015;Costagliola et al 2015;Jiang et al 2017;Rico-Villas et al 2021). HC 3 N lines are considered dense (>10 4 cm −3 ) molecular gas tracers with fainter flux than HCN, HCO + , and HNC (e.g., Wang et al 2004;Aladro et al 2011;Meier et al 2011).…”
Section: Other Faintermentioning
confidence: 99%
“…The same galaxy was then re-investigated by Costagliola et al (2015) who highlighted the importance of HC 3 N in luminous infrared galaxies (LIRG). In recent years, this species has been revealed in other extra-galactic sources: IC 342, M66 and NGC 660 (Jiang et al 2017), NGC 1097 (Martín et al 2015), and in the nearby LIRG Mrk 231 by Aalto et al (2012). Lindberg et al (2011) published a survey of 13 galaxies in which HC 3 N has been detected.…”
Section: Introductionmentioning
confidence: 99%